Concentration‐ and Solvent‐Dependent Photochemical Instability of 6, 13‐Bis(triisopropysilylethynyl)pentacene. Issue 7 (3rd April 2014) - Abu‐Sen, Laila; Morrison, John J.; Horn, Andrew B.; Yeates, Stephen G.
<x xml:space="preserve">Abstract</x> The solvent‐ and concentration‐dependent photostability of TIPS‐pentacene in solution is directly related to the efficiency of singlet‐state deactivation by a combination of pairwise interactions and quenching at low concentration. At higher concentrations, further increases in stability suggest the onset of aggregation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>